The effectiveness of the flipped classroom on mathematical higher order thinking skills: a meta-analysis - Julham Hukom; Said Sudi Khassim (Creative Smart Visionary, 2026)
Higher order thinking skills (HOTS) are a core competency in 21st-century mathematics education, yet they remain difficult to achieve through conventional instruction. The flipped classroom has been proposed as an alternative that reverses the allocation of learning time so that higher order thinking activities can be facilitated more intensively in class. This study quantitatively synthesized the magnitude of the flipped classroom effect on mathematical HOTS through a meta-analysis. Eleven effect sizes drawn from experimental and quasi-experimental studies with a total of 1,091 participants were analyzed using a random-effects model with Hedges g as the effect size index. The pooled effect size was g = 0.82 (95% CI [0.59, 1.05]; p < 0.001), which is large, with moderate to substantial heterogeneity (I-squared = 67.6%). Publication bias tests indicated robust findings. Moderator analysis showed that education level, country, and flipped classroom variant acted as significant moderators, whereas the HOTS domain did not. These findings strengthen the evidence that the flipped classroom is effective for developing mathematical HOTS across contexts.